The Concept of Neo-Traditional Islam in the Perennial Philosophy of Seyyed Hossein Nasr - Encung Encung (Al-Falsafah: Jurnal Pemikiran dan Filsafat Islam, 2026)
This study examines the concept of Neo-Traditional Islam within the framework of Perennial Philosophy of Nasr, particularly as articulated by Seyyed Hossein Nasr in his modernity thought. Neo-Traditional Islam emerges as a critical response to secular modernity, which is perceived to have desacralized knowledge and fragmented the metaphysical foundations of human existence. Using a qualitative library-based research method, this paper analyzes Nasr’s major works on tradition, Sufism, and metaphysics to explore the epistemological and ontological dimensions of his thought. Utilate hermeneutical method to interpretate the thought of him this research aim to find defficult thought of Nasr in describing his concept upon his several books. The findings indicate that Neo-Traditional Islam emphasizes the centrality of revelation, the revival of sacred knowledge (scientia sacra), and the intellectual function of the ‘aql understood as the spiritual intellect rather than mere rationality. Within the perspective of Perennial Philosophy, religion is viewed as possessing a transcendent unity (sophia perennis) that underlies its diverse historical expressions. This approach affirms Islam as a living and continuous tradition capable of engaging modern challenges without compromising its sacred foundations. Ultimately, Neo-Traditional Islam offers a profound critique of materialistic and reductionist worldviews while proposing a spiritually grounded alternative for contemporary civilization.